Mergers And Acquisitions in The Hightech Company: A Bibliometric Review and Future Research Directions - Sindhu Priyo Windoko; Atika Sanjani Ramadina; Muhammad Haris Jauhari; Enny Susilowati Mardjono; Ulfah Nurul Fauziah (International Journal of Business and Management Technology in Society, 2023)
Purpose – This study is aimed to shows the research interest trend about mergers and acquisitions (M&A) in high-tech companies. Methodology – This research uses a combination of bibliometric analysis and content analysis. Bibliometric analysis is fundamentally concerned with the quantitative and statistical analysis of a set of connected documents using several bibliometric indicators that offer an overall summary of a research area. While, a structured SLR sticks to a strict scientific design based on clear, prespecified and reproducible methods. Findings – A technology company's growth options affect its likelihood of being acquired, and companies with high growth options tend to choose organic growth over acquisitions with other technology companies. M&A size has an “inverted U”-shaped relationship with post-acquisition innovation performance, and post-acquisition R&D investment can moderate the relationship. Increasing the level of post-acquisition R&D investment can increase technology uptake capacity and extend the positive effect interval of M&A measures on post-acquisition innovation performance. Research limitations – This study only covers research published related to strategic planning in digital marketing, the data selected only use synta strategic, and the co-occurrence analysis was used to present the conceptual structure in this study. Practical implications – This research will help practitioners to understand the basis of job satisfaction in textile factory workers and contribute to the scientific community by providing thematic maps and recommendations for future research of this field of study.